Mobile platform for rapid sub–picogram-per-milliliter, multiplexed, digital droplet detection of proteins - Yelleswarapu, Venkata; Buser, Joshua R.; Haber, Margalit; Baron, Jonathan; Inapuri, Eshwar; Issadore, David (Proceedings of the National Academy of Sciences - PNAS, 2019)
Digital droplet assays—in which biological samples are compartmentalized into millions of femtoliter-volume droplets and interrogated individually—have generated enormous enthusiasm for their ability to detect biomarkers with single-molecule sensitivity. These assays have untapped potential for point-of-care diagnostics but are currently mainly confined to laboratory settings, due to the instrumentation necessary to serially generate, control, and measure tens of millions of droplets/compartments. To address this challenge, we developed an optofluidic platform that miniaturizes digital assays into a mobile format by parallelizing their operation. This technology is based on three key innovations: (i) the integration and parallel operation of a hundred droplet generators onto a single chip that operates >100× faster than a single droplet generator, (ii) the fluorescence detection of droplets at >100× faster than conventional in-flow detection using time domain-encoded mobile phone imaging, and (iii) the integration of on-chip delay lines and sample processing to allow serum-to-answer device operation. To demonstrate the power of this approach, we performed a duplex digital ELISA. We characterized the performance of this assay by first using spiked recombinant proteins in a complex media (FBS) and measured a limit of detection, 0.004 pg/mL (300 aM), a 1,000× improvement over standard ELISA and matching that of the existing laboratory-based gold standard digital ELISA system. We additionally measured endogenous GM-CSF and IL6 in human serum from n = 14 human subjects using our mobile duplex assay, and showed excellent agreement with the gold standard system (R² = 0.96).